Is transthoracic ultrasound (TUS) a reliable predictor of the nature of pleural and peripheral pulmonary lesions? Correlation with cyto-histological findings - Mohamed H. Faheem (The Egyptian Journal of Radiology and Nuclear Medicine, 2019)
Abstract Background We focused on determining the most reliable transthoracic ultrasound (TUS) criteria that can predict malignancy of the pleural and peripheral pulmonary lesions and correlating our data with CT and cyto-histological findings. Sixty-nine patients (38 males and 31 females) were enrolled in our prospective study. They were divided into group I (48 patients), which included patients with pleural effusion, and group II (21 patients), which included patients with peripheral pulmonary lesions. All patients underwent chest X-ray (postero-anterior and lateral views), transthoracic ultrasound (TUS), CT chest, guided Tru-cut or surgical biopsies and histopathology, and/or needle aspiration and cytology. Results In group I, the presence of pleural nodularity was a predictor of malignancy with significant statistical difference (b value < 0.001) and receiver operating curve (ROC) curve analysis showed pleural thickening cutoff value of 7 mm at a maximum combined sensitivity and specificity of 75% and 80% respectively and area under the curve 0.825. In group II, distorted intralesional vascular pattern, pleural, and chest wall invasion were statistically significant ultrasonographic malignant predictors (b values are <0.001, 0.016, and 0.004 respectively). Conclusion TUS is a valuable and safe complementary method in differentiation between benign and malignant pleural effusion and peripheral pulmonary lesions but is not a substitute for CT.